Pro- and anti-inflammatory cytokine responses to a 164-km road cycle ride in a hot environment - Luk, H. Y.; Levitt, D. E.; Lee, E. C.; Ganio, M. S.; McDermott, B. P.; Kupchak, B. R.; McFarlin, B. K.; Hill, D. W.; Armstrong, L. E.; Vingren, J. L. (European Journal of Applied Physiology, 2016)
Purpose: The purpose of this study was to examine the circulating cytokine response to a recreational 164-km road cycling event in a high ambient temperature and to determine if this response was affected by self-paced exercise time to completion. Methods: Thirty-five men and five women were divided into tertiles based on time to complete the cycling event: slowest (SLOW), moderate (MOD), and fastest (FAST) finishers. Plasma samples were obtained 1-2 h before (PRE) and immediately after (IP) the event. A high-sensitivity multiplex assay kit was used to determine the concentration of plasma anti-inflammatory cytokines (IL-4, IL-5, IL-10, IL-13) and pro-inflammatory cytokines (IL-1ß, IL-2, IL-6, IL-7, IL-8, IL-12, GM-CSF, IFN-gamma, and TNF-a). Results: The concentration of plasma IL-10 increased significantly (p < 0.05) in FAST and MOD groups and had no change in the SLOW group in response to a 164-km cycling event in the hot environment. Other cytokine responses were not influenced by the Time to completion. Pro-inflammatory cytokines IL-1ß, IL-2, GM-CSF, and TNF-a decreased; whereas, IL-6 and IL-8 increased from PRE to IP. Additionally, anti-inflammatory cytokines IL-4 and IL-13 decreased. Conclusions: Completion of a 164-km cycling event induced substantial changes in circulating pro- and anti-inflammatory cytokine concentrations. Time to completion appears to have a greater influence on the systemic IL-10 response than the environmental condition; however, it is possible that a threshold for absolute intensity must be reached for environmental conditions to affect the IL-10 response to exercise. Thus, cyclists from the FAST/MOD groups appear more likely to experience an acute transient immune suppression than cyclists from the SLOW group.